Factors of the Use of AI Technology Influencing Community Security in UAE - Almakki Alhajeri, Amna Ali Abdulla Mohammed; Mohd Safian, Edie Ezwan (International Journal of Sustainable Construction Engineering and Technology, 2023)
This paper presents a study on addressing 27 factors of the use of AI technology influencing community security in UAE. The factors are categorised in five groups namely AI Ethics; Compatibility; Complexity; Management support; and Staff Capability. This study used a questionnaire survey with the Abu Dhabi Police department as a case study for community security. The survey managed to 138 valid responses and analysed descriptively. In deciding the level of influence. It was found that 16 of the factors are having very high influence while the others are having high influence. In ranking analysis, it was found that the highest rank of AI technology’s factors influence community security in each group is for compatibility (COMPA5), which underscores the harmony between an individual’s skills and the employed AI technologies; complexity (COMPLEX2), highlighting the efficiency of AI-driven systems, particularly in rapid knowledge acquisition through online conferencing; management support (MS4), spotlighting the proactive endorsement and direction from organizational management in AI security technology implementation; ethics of AI (ETH3), accentuating the individual’s commitment to ethical considerations while employing AI security technologies; and staff capability (SC2), which reflects the individual’s proficiency and competence in effectively harnessing AI technologies for enhanced community security measures. Collectively, these factors shed light on the multifaceted ways AI technologies impact and shape the realm of UAE community security.